Taxonomic review of Copella (Characiformes: Lebiasinidae) with an identification key for the species. - Manoela M F Marinho; Naércio A Menezes (PLoS ONE, 2017)
A taxonomic review of Copella is presented based on the analysis of the type material of all nominal species and extensive material from South American drainages. Six out of ten nominal species are recognized as valid: Copella arnoldi, C. callolepis, C. compta, C. eigenmanni, C. nattereri, and C. vilmae. Copella carsevennensis is a junior synonym of C. arnoldi, C. nigrofasciata and 'Nannostomus' stigmasemion are junior synonyms of C. callolepis, C. metae is junior synonym of C. eigenmanni, and C. meinkeni is junior synonym of C. nattereri. Species of Copella occur in the rio Amazonas and Orinoco basins, and coastal drainages of Guyana, French Guiana, Surinam, and Venezuela. An identification key is provided.